Stress in ion exchanged soda-lime silicate and sodium aluminosilicate glasses: Experimental and theoretical comparison - Macrelli, Guglielmo; Ozben, Nahide; Kayaalp, Ahmet Caner; Celikbilek Ersundu, Miray; Sokmen, Ilkay (WILEY PERIODICALS, INC, 2020)
Glass samples of two different chemical compositions were strengthened by ion exchange. Residual stress profiles were experimentally determined by differential surface refractometry. The experimental results were compared with values theoretically predicted by a formalized viscoelastic mathematical model incorporating both stress buildup and stress relaxation contributions. The comparison exhibited a remarkable agreement both in terms of strengthening characteristics and stress profiles curves between experimentally measured and theoretically predicted values. The mathematical model incorporated terms directly linked to selected relaxation mechanisms either isochoric shear stress driven and fast relaxation. The comparison demonstrated the relevance of the stress relaxation mechanisms for the different glass chemical compositions. The approach presented in this study will allow the prediction of the mechanical behavior of chemically strengthened glass starting from its chemical composition together with the ion exchange process parameters.
Keywords: chemical strengthening; glass; ion exchange; residual stress; stress relaxation; RELAXATION; PROFILES; BUILDUP; Materials Science